Transient hypoxemia chronically disrupts maturation of preterm fetal ovine subplate neuron arborization and activity - McClendon, E; Shaver, DC; Degener-O'Brien, K; Gong, X; Nguyen, T; Hoerder-Suabedissen, A; Molnár, Z; Mohr, C; Richardson, BD; Rossi, DJ; Back, SA (Society for Neuroscience, 2017)
Preterm infants are at risk for a broad spectrum of neurobehavioral disabilities associated with diffuse disturbances in cortical growth and development. During brain development, subplate neurons (SPNs) are a largely transient population that serves a critical role to establish functional cortical circuits. By dynamically integrating into developing cortical circuits they assist in consolidation of intra and extracortical circuits. Although SPNs reside in close proximity to cerebral white matter, which is particularly vulnerable to oxidative stress, the susceptibility of SPNs remains controversial. We determined SPN responses to two common insults to the preterm brain, hypoxia-ischemia and hypoxia. We employed a preterm fetal sheep model using both sexes that reproduces the spectrum of human cerebral injury and abnormal cortical growth. Unlike oligodendrocyte progenitors, SPNs displayed pronounced resistance to early or delayed cell death from hypoxia or hypoxia-ischemia. We thus explored an alternative hypothesis that these insults alter the maturational trajectory of SPNs. We employed DiOlistic labeling to visualize the dendrites of SPNs selectively labeled for complexin-3. SPNs displayed reduced basal dendritic arbor complexity that was accompanied by chronic disturbances in SPN excitability and synaptic activity. SPN dysmaturation was significantly associated with the level of fetal hypoxemia and metabolic stress. Hence, despite the resistance of SPNs to insults that trigger white matter injury, transient hypoxemia disrupted SPN arborization and functional maturation during a critical window in cortical development. Strategies directed at limiting the duration or severity of hypoxemia during brain development may mitigate disturbances in cerebral growth and maturation related to SPN dysmaturation.SIGNIFICANCE STATEMENTThe human preterm brain commonly sustains blood flow and oxygenation disturbances that impair cerebral cortex growth and cause life-long cognitive and learning disabilities. We investigated the fate of subplate neurons (SPNs), which are a master regulator of brain development that plays critical roles in establishing cortical connections to other brain regions. We utilized a preterm fetal sheep model that reproduces key features of brain injury in human preterm survivors. We analyzed the responses of fetal SPNs to transient disturbances in fetal oxygenation. We discovered that SPNs are surprisingly resistant to cell death from low oxygen states, but acquire chronic structural and functional changes that suggest new strategies to prevent learning problems in children and adults that survive preterm birth.